High-throughput single-molecule RNA imaging analysis reveals heterogeneous responses of cardiomyocytes to hemodynamic overload. (March 2019) - Satoh, Masahiro; Nomura, Seitaro; Harada, Mutsuo; Yamaguchi, Toshihiro; Ko, Toshiyuki; Sumida, Tomokazu; Toko, Haruhiro; Naito, Atsuhiko T.; Takeda, Norifumi; Tobita, Takashige; Fujita, Takanori; Ito, Masamichi; et al.
Abstract: Background: The heart responds to hemodynamic overload through cardiac hypertrophy and activation of the fetal gene program. However, these changes have not been thoroughly examined in individual cardiomyocytes, and the relation between cardiomyocyte size and fetal gene expression remains elusive. We established a method of high-throughput single-molecule RNA imaging analysis of in vivo cardiomyocytes and determined spatial and temporal changes during the development of heart failure. Methods and results: We applied three novel single-cell analysis methods, namely, single-cell quantitative PCR (sc-qPCR), single-cell RNA sequencing (scRNA-seq), and single-molecule fluorescence in situ hybridization (smFISH). Isolated cardiomyocytes and cross sections from pressure overloaded murine hearts after transverse aortic constriction (TAC) were analyzed at an early hypertrophy stage (2 weeks, TAC2W) and at a late heart failure stage (8 weeks, TAC8W). Expression of myosin heavy chain β ( Myh7 ), a representative fetal gene, was induced in some cardiomyocytes in TAC2W hearts and in more cardiomyocytes in TAC8W hearts. Expression levels of Myh7 varied considerably among cardiomyocytes. Myh7 -expressing cardiomyocytes were significantly more abundant in the middle layer, compared with the inner or outer layers of TAC2W hearts, while such spatial differences were not observed in TAC8W hearts. Expression levels of Myh7 were inversely correlated with cardiomyocyte size and expression levels of mitochondria-related genes. Conclusions: We developed a new image-analysis pipeline to allow automated and unbiased quantification of gene expression at the single-cell level and determined the spatial and temporal regulation of heterogenous Myh7 expression in cardiomyocytes after pressure overload. Highlights: Novel pipeline combines scRNA-seq and smFISH with high-throughput image analysis. Stress response shown by increased Myh7 expression was spatially heterogeneous. Mitochondria-related genes inversely correlated with Myh7 in scRNA-seq data. Decreased cell size in Myh7 -positive cells suggests energy metabolism crisis.